Socio-demographic Profile of the Population Aged 65 and Over - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)